Programmed Death-Ligand 1 Expression Potentiates the Immune Modulatory Function Of Myeloid-Derived Suppressor Cells in Systemic Lupus Erythematosus - Park, Min-Jung; Baek, Jin-Ah; Choi, Jeong Won; Jang, Se Gwang; Kim, Da-Som; Park, Sung-Hwan; Cho, Mi-La; Kwok, Seung-Ki (Frontiers in Immunology, 2021)
Multiple studies have explored the potential role of programmed death-ligand 1 (PD-L1) as a mediator of Myeloid-derived suppressor cells (MDSCs) effects in various cancers. However, the role PD-L1 expression in MDSCs on autoimmune disease is still largely unknown.This study was undertaken to whether MDSC expressing PD-L1 have more potent immunoregulatory activity and control autoimmunity more effectively in two murine models of lupus (MRL/lpr mice and Roquinsan/san mice). The populations of MDSC were increased in peripheral blood of lupus patients. The mRNA levels of immunosuppressive molecules were profoundly decreased in MDSCs from lupus patients and mice. Co-culture with splenocytes showed that PD-L1 expressing MDSCs from control mice expand both Treg cells and regulatory B cells more potently. Infusion of PD-L1 expressing MDSCs reduced autoantibody levels and degree of proteinuria and improved renal pathology of two animal models of lupus. Moreover, PD-L1 expressing MDSCs therapy can suppress double negative (CD4-CD8-CD3+) T cells, the major pathogenic immune cells and follicular helper T cells in MRL/lpr mice, and podocyte damage. Our results indicate PD-L1 expressing MDSCs have more potent immunoregualtory activity and ameliorate autoimmunity more profoundly. These findings suggest PD-L1 expressing MDSCs be a promising therapeutic strategy targeting systemic autoimmune diseases.